Prostate Cancer Screening and Incidence among Aging Persons Living with HIV. Issue 2 (24th February 2022) - Leapman, Michael S.; Stone, Kimberly; Wadia, Roxanne; Park, Lesley S.; Gibert, Cynthia L.; Goetz, Matthew B.; Bedimo, Roger; Rodriguez-Barradas, Maria; Shebl, Fatma; Justice, Amy C.; Brown, Sheldon T.; Crothers, Kristina; et al.
Abstract : Purpose: The risk of prostate cancer among persons living with human immunodeficiency virus (PWH) is not well understood and may be obscured by different opportunities for detection. Materials and Methods: We identified 123, 472 (37, 819 PWH and 85, 653 comparators) men enrolled in the Veterans Aging Cohort Study, a prospective national cohort of PWH and demographically matched, uninfected comparators in 2000–2015. We calculated rates of prostate specific antigen (PSA) testing by human immunodeficiency virus (HIV) status and fit multivariable Poisson models comparing the rates of PSA testing, prostate biopsy, and cancer incidence. Results: The mean age at enrollment was 52 years. Rates of PSA testing were lower in PWH versus uninfected comparators (0.58 versus 0.63 tests per person-year). Adjusted rates of PSA screening and prostate biopsy were lower among PWH (incidence rate ratio [IRR] 0.87, 95% CI 0.75–0.84 and IRR 0.79 95% CI 0.74–0.83, respectively). The crude IRR for prostate cancer was lower in PWH versus controls (IRR 0.90, 95% CI 0.83–0.97). However, in a multivariable model adjusting for PSA testing, cancer incidence was similar by HIV status (IRR=0.93, 95% CI 0.86–1.01, p=0.08). Among patients who received a prostate biopsy, incidence of prostate cancer did not differ significantly by HIV status (IRR 1.06, 95% CI 0.98–1.15, p=0.15). Among incident cancers, there were significant differences in the distributions of Gleason grade (p=0.05), but not cancer stage (p=0.14) by HIV status. Conclusions: When accounting for less PSA testing among PWH, the incidence of prostate cancer was similar by HIV status. These findings suggest that less screening contributed to lower observed incidence of prostate cancer in PWH.